Team Relationship and Knowledge Management in Construction Projects in Thailand Part 1: Network Relationship Analysis Using UCINET Software - Boonyanan, Archan; Robinson, Herbert; Naoum, Shamil; Fong, Daniel (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Problematic relationship within fragmented team structures and inefficient multi-stage project development processes are the two major issues that affect project development performance in the construction industry. The problems are particularly apparent In Thailand’s developing economy. This paper focuses on the study of relationship among construction project team members at the pre-design appraisal development stage as the first step to improve the competitiveness of project development in Thailand’s construction industry. Recently completed large commercial residential projects in Bangkok’s central business district were used as case studies. For the field research, semi-structured interviews were conducted with a selection of client organisations and key project members using a standardised questionnaire to collect relevant quantitative and qualitative data. UCINET, the social network analysis software, was implemented to analyse quantitative data to reveal the relationship characteristics. The transformed aggregate scores of strength and satisfaction of relationship, as well as some of the project network characteristics like low network density (0.2045 out of 1.000) in selected case study projects, did not appear to be very accommodating to the creation of good relationship. Other network characteristics, including high reciprocity (68.75%), above average reachability (8 out of 11), relatively short (1.405) average geodesic distance and small degree centralisation (27% out degree and 37% in degree) suggested a close relationship among key project members. Moreover, supportive personal and subgroup characteristics such as low to average (1 to 6 out of 11) out and in degree centrality and a high clustering coefficients (0.725 out of 1.000) were considered as the key factors to achieving effective knowledge creation and transfer. This will be explored further in part 2 of this research.